PENERAPAN STRATEGI PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KETERAMPILAN PRODUKTIF DI PKBM RAWASARI - Puji Hadiyanti (Jurnal Ilmiah Visi, 2011)
The development of human potential through community-based educational activities aims at understanding and identifying needs and solutions that make the community itself taking into account the potential that exists in the environment. Therefore PKBM (Community Learning Center) is one of the institutions to explore and develop community-based education. The objective of this study to describe the implementation of the strategy undertaken by PKBM Rawasari in empowering the community through productive skills. The study includes the selection of the target area programs, socialization of the programs, program implementation and monitoring and evaluation of community empowerment, as well as its influence on the economic changes in the society. The method used was descriptive qualitative. The collected data were analyzed descriptively and qualitatively. The data were analyzed using percentage calculation to be interpreted and described in words.The results of the study show that the productive skills program held PKBM Rawasari is not an optimal strategy in a holistic community empowerment. However, some benefits have been felt by the program participants.